2021
DOI: 10.1111/jmft.12566
|View full text |Cite
|
Sign up to set email alerts
|

Using systemic interventions to reduce intimate partner violence or child maltreatment: A systematic review of publications between 2010 and 2019

Abstract: This systematic review seeks to understand the effectiveness of systemic interventions to reduce Intimate Partner Violence (IPV) or child maltreatment published between January 2010 and December 2019. We found nine studies reviewing systemic interventions for IPV and 12 studies reviewing systemic interventions for child maltreatment. In our discussion, we added relevant articles published before 2010 to determine the overall state of the evidence for these interventions. We determined that parent training prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…We reviewed outcome research studies published from 2010 to 2019 in English-language journals, focusing specifically on the collection of studies included within 11 articles in this special issue. Studies were reviewed across the following mental health topics: infant and early childhood mental health (IECMH; Kaminski et al, 2022), disruptive behavior problems (Sheidow et al, 2022), attention-deficit/hyperactivity disorder (ADHD; Babinski & Sibley, 2022), anxiety disorders (Goger & Weersing, 2022), depressive and bipolar disorders , suicidal ideation and behavior (Frey et al, 2022), substance use disorders (Hogue et al, 2022), traumatic event exposure (McWey, 2022), intimate partner violence and child maltreatment (Stith et al, 2022), couple relationship education (Markman et al, 2022), and couple relationship distress (Doss et al, 2022). Although physical health was also featured in the special issue (Lamson et al, 2022), we did not review physical health interventions as we considered these interventions to have important methodological differences meriting their own review.…”
Section: Methodsmentioning
confidence: 99%
“…We reviewed outcome research studies published from 2010 to 2019 in English-language journals, focusing specifically on the collection of studies included within 11 articles in this special issue. Studies were reviewed across the following mental health topics: infant and early childhood mental health (IECMH; Kaminski et al, 2022), disruptive behavior problems (Sheidow et al, 2022), attention-deficit/hyperactivity disorder (ADHD; Babinski & Sibley, 2022), anxiety disorders (Goger & Weersing, 2022), depressive and bipolar disorders , suicidal ideation and behavior (Frey et al, 2022), substance use disorders (Hogue et al, 2022), traumatic event exposure (McWey, 2022), intimate partner violence and child maltreatment (Stith et al, 2022), couple relationship education (Markman et al, 2022), and couple relationship distress (Doss et al, 2022). Although physical health was also featured in the special issue (Lamson et al, 2022), we did not review physical health interventions as we considered these interventions to have important methodological differences meriting their own review.…”
Section: Methodsmentioning
confidence: 99%
“…The evidence regarding interventions for couples where IPV is present is generally weak, with systematic reviews indicating high variability in design, few comparative studies of generally lower quality, and mixed results [ 65 •, 66 , 67 ]. A key consideration is ensuring that the intervention does not lead to additional harms to the survivor; thus, studies generally showing some benefit are those in which the violence is situational and/or bi-directional, or in which other related issues, such as substance use, are a key factor.…”
Section: Resultsmentioning
confidence: 99%
“…This includes an analysis of the function of violence in a particular family, as well as how the complex patterns of communication, narratives and feedback loops perpetuates and maintains violent behaviour between different parts of the system (Sammut Scerri et al, 2017). A recent systematic review found evidence to support the use of family therapy in the reduction of IPV (Stith et al, 2022). Ecological models can also take wider social factors into account, linking immediate familial risk factors with the poverty, mental health problems and substance misuse problems that underpin family and community level violence (Hisham et al, 2021).…”
Section: Resultsmentioning
confidence: 99%